ANALISIS KUALITAS HADIS RIWAYAT SHAHIH MUSLIM NO. 2700: KAJIAN SANAD DAN MATAN - Utami, Fallya Putri (Universitas Islam Indonesia, 2025)
Hadith has a central position as the second source of Islamic law after the Qur'an. One of the important hadiths is Saheeh Muslim No. 2700 which explains the virtues of congregational dhikr, including its impact in the form of calmness, mercy, angelic protection, and the attention of Allah SWT. This study aims to analyze the quality of the hadith through the takhrij method, which includes the evaluation of sanad and matan. The results of the study show that the main sanad of this hadith is classified as munqathi (disconnected) because of the significant time gap between several awi, so it does not meet the criteria of ittishal. However, the existence of mutabi' and shuahid paths in other histories such as Sunan Daud and Musnad Ahmad strengthens the validity of matan. In terms of matan, this hadith does not contradict Islamic principles and has high moral and spiritual value. This study emphasizes the importance of a scientific approach in assessing the quality of hadith, and recommends further exploration to strengthen the study of hadith in various aspects of life.